PENGARUH INDEPENDENSI AUDITOR, GAYA KEPEMIMPINAN, DAN MOTIVASI KERJA TERHADAP KINERJA AUDITOR (Studi Kasus Pada Kantor Akuntan Publik di Kota Semarang) - Risman Taufik S, 16.05.72.0001; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2019)
Auditor performance is something that very important for Public Accounting Firm. Whether Public Accounting Firm is good or not is determined by auditor’s performance. This research aimed to examine and analyzes the effect of auditor independence, leadership style, and work motivation on auditor performance with organizational commitment as an intervening variable. The population which became the object of this study is the auditor who works for the Public Accounting Firm in Semarang City, which registered by the Indonesian Institute of Certified Public Accountants (IAPI). This research use Convinience Sampling method. The sample in this study included 14 KAP with 86 respondents. Data analysis used a path analysis model with SPSS 16.0 program. The results of this research found that the auditor independence variable has a positive effect on organizational commitment, leadership style does not affect organizational commitment, work motivation does not affect organizational commitment, auditor independence does not affect auditor performance, leadership style has a positive effect on auditor performance, work motivation has no effect on auditor performance, and organizational commitment has no effect on auditor performance.